Plant virus diversity in bee and pollen samples from apple (Malus domestica) and sweet cherry (Prunus avium) agroecosystems - Smadi, Malek; Lee, Eunseo; Phelan, James; Wang, Aiming; Bilodeau, Guillaume J.; Pernal, Stephen F.; Guarna, M. Marta; Rott, Mike; Griffiths, Jonathan S. (Frontiers in Plant Science, 2024)
Introduction Honey bee (Apis mellifera) pollination is widely used in tree fruit production systems to improve fruit set and yield. Many plant viruses can be associated with pollen or transmitted through pollination, and can be detected through bee pollination activities. Honey bees visit multiple plants and flowers in one foraging trip, essentially sampling small amounts of pollen from a wide area. Here we report metagenomics-based area-wide monitoring of plant viruses in cherry (Prunus avium) and apple (Malus domestica) orchards in Creston Valley, British Columbia, Canada, through bee-mediated pollen sampling. Methods Plant viruses were identified in total RNA extracted from bee and pollen samples, and compared with profiles from double stranded RNA extracted from leaf and flower tissues. CVA, PDV, PNRSV, and PVF coat protein nucleotide sequences were aligned and compared for phylogenetic analysis. Results A wide array of plant viruses were identified in both systems, with cherry virus A (CVA), prune dwarf virus (PDV), prunus necrotic ringspot virus (PNRSV), and prunus virus F (PVF) most commonly detected. Citrus concave gum associated virus and apple stem grooving virus were only identified in samples collected during apple bloom, demonstrating changing viral profiles from the same site over time. Different profiles of viruses were identified in bee and pollen samples compared to leaf and flower samples reflective of pollen transmission affinity of individual viruses. Phylogenetic and pairwise analysis of the coat protein regions of the four most commonly detected viruses showed unique patterns of nucleotide sequence diversity, which could have implications in their evolution and management approaches. Coat protein sequences of CVA and PVF were broadly diverse with multiple distinct phylogroups identified, while PNRSV and PDV were more conserved. Conclusion The pollen virome in fruit production systems is incredibly diverse, with CVA, PDV, PNRSV, and PVF widely prevalent in this region. Bee-mediated monitoring in agricultural systems is a powerful approach to study viral diversity and can be used to guide more targeted management approaches.